Hospital-Acquired Phaeohyphomycosis Due to Exserohilum rostratum in a Child with Leukemia - Maude Saint-Jean; Guy St-Germain; Céline Laferrière; Bruce Tapiero (Canadian Journal of Infectious Diseases and Medical Microbiology)
The present study describes a case of cutaneous phaeohyphomycosis caused by Exserohilum rostratum in a child undergoing treatment for leukemia. The infection was possibly due to contaminated intravenous dressings and was successfully treated with surgical excision combined with liposomal amphotericin B. Consequently, new infection control policies have been implemented at CHU Sainte-Justine (Montreal, Quebec).